-7(t-7)-3(3t+1)=-2

Simple and best practice solution for -7(t-7)-3(3t+1)=-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7(t-7)-3(3t+1)=-2 equation:


Simplifying
-7(t + -7) + -3(3t + 1) = -2

Reorder the terms:
-7(-7 + t) + -3(3t + 1) = -2
(-7 * -7 + t * -7) + -3(3t + 1) = -2
(49 + -7t) + -3(3t + 1) = -2

Reorder the terms:
49 + -7t + -3(1 + 3t) = -2
49 + -7t + (1 * -3 + 3t * -3) = -2
49 + -7t + (-3 + -9t) = -2

Reorder the terms:
49 + -3 + -7t + -9t = -2

Combine like terms: 49 + -3 = 46
46 + -7t + -9t = -2

Combine like terms: -7t + -9t = -16t
46 + -16t = -2

Solving
46 + -16t = -2

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '-46' to each side of the equation.
46 + -46 + -16t = -2 + -46

Combine like terms: 46 + -46 = 0
0 + -16t = -2 + -46
-16t = -2 + -46

Combine like terms: -2 + -46 = -48
-16t = -48

Divide each side by '-16'.
t = 3

Simplifying
t = 3

See similar equations:

| In(x)+In(2x)=2 | | 5x+4=20+3x | | 5x^2-29x+20=0 | | 2x-10y=5 | | 8y=12.8 | | 2y=11x-5 | | 6x+4x-9=17 | | -65-4= | | 525+0.21x=528+0.13x | | 3y^2-27y= | | y=a+b+c/5 | | 525+0.21=585+0.13 | | a+b+c/5 | | Y=0.1(3)x | | 0.1(0.1x+0.3)=-0.2 | | 1/2k+2=5+5/4 | | x^(4/3)-5x^(2/3)+6=0 | | 9x-80=3x-14 | | 2x^2+kx+11=0 | | -3(6y-4)=4(1-5y)+9 | | 5x-3=12x+45 | | 9+3x=39 | | -3x+5=-8x+25 | | 6x-8=x-8 | | 8(x+6)=2(x+42) | | 51-5x=4x+19 | | 4(x-6)=46-6x | | -4/7x-28 | | 2x-1=44-7x | | 14-10x=86-38x | | -2x-3+x=-2x+4-x | | 109-3x=24x+19 |

Equations solver categories